Electrically controlled transdermal delivery of naproxen and indomethacin from porous cis‐1, 4‐polyisoprene matrix. Issue 2 (16th August 2021) - Ruangmak, Kamonpan; Paradee, Nophawan; Niamlang, Sumonman; Sakunpongpitiporn, Phimchanok; Sirivat, Anuvat
Abstract: This study is focused on the inquiry of using a porous polymeric structure to absorb and release transdermally two drugs through a skin from deproteinized natural rubber latex (DPNR). The porous DPNR films were fabricated from the internal formation of surfactant micelles and their subsequent leaching out to generate porous structures. The pore size of DPNR films increased with increasing surfactant amount. The model drugs were naproxen and indomethacin; their releases and release‐permeations were investigated under the effects of surfactant amount, electrical potential, and drug size. Without electric field, the drug release mechanism was mainly driven by concentration gradient. The higher amount of drug released was obtained from the matrix with a larger pore size. Under electric field, the higher amounts of drug release were obtained in the shorter drug release durations, via the electrorepulsive force between the negatively charged drugs and the cathode electrode. The molecular drug size was a factor for the drug absorption, release rate and amount. For the drug release‐permeation experiment through the pig skin, there were two release‐permeation periods as governed by the combination of concentration gradient and swelling in the first period, and the matrix erosion in the second period. The fabricated porous DPNR films have been shown here to be potential to be used as a transdermal patch with electrically controllable drug release rate, amount and duration along with the facile drug‐matrix loading and absorption. Abstract :